Sex differences in the effect of chronic delivery of the buprenorphine analogue BU08028 on heroin relapse and choice in a rat model of opioid maintenance. (27th October 2021) - Bossert, Jennifer M.; Townsend, E. Andrew; Altidor, Lindsay K‐P; Fredriksson, Ida; Shekara, Aniruddha; Husbands, Stephen; Sulima, Agnieszka; Rice, Kenner C.; Banks, Matthew L.; Shaham, Yavin
Abstract : Background and Purpose: Maintenance treatment with opioid agonists (buprenorphine, methadone) decreases opioid use and relapse. We recently modelled maintenance treatment in rats and found that chronic delivery of buprenorphine or the μ opioid receptor partial agonist TRV130 decreased relapse to oxycodone seeking and taking. Here, we tested the buprenorphine analogue BU08028 on different heroin relapse‐related measures and heroin versus food choice. Experimental Approach: For relapse assessment, we trained male and female rats to self‐administer heroin (6 h·day −1, 14 days) in Context A and then implanted osmotic minipumps containing BU08028 (0, 0.03 or 0.1 mg·kg −1 ·d −1 ). Effects of chronic BU08028 delivery were tested on (1) incubation of heroin‐seeking in a non‐drug Context B, (2) extinction responding reinforced by heroin‐associated discrete cues in Context B, (3) reinstatement of heroin‐seeking induced by re‐exposure to Context A and (4) re‐acquisition of heroin self‐administration in Context A. For choice assessment, we tested the effect of chronic BU08028 delivery on heroin versus food choice. Key Results: Chronic BU08028 delivery decreased incubation of heroin seeking. Unexpectedly, BU08028 increased re‐acquisition of heroin self‐administration selectively in females. Chronic BU08028 had minimal effects on context‐induced reinstatement and heroin versus food choice in both sexes. Finally, exploratory post hoc analyses suggest that BU08028 decreased extinction responding selectively in males. Conclusions and Implications: Chronic BU08028 delivery had both beneficial and detrimental, sex‐dependent, effects on different triggers of heroin relapse and minimal effects on heroin choice in both sexes. Results suggest that BU08028 would not be an effective opioid maintenance treatment in humans.